2022
DOI: 10.47750/pnr.2022.13.s06.291
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Serum levels of Leptin,CRP and Lipid profile in Hypothyroid Women in Kirkuk city/Iraq

Abstract: Leptin is a hormone primarily produced by the adipose tissue in proportion to the size of fat stores with a primary function in the control of lipid reserves,this study aimed to evaluate the influence of hypothyroidisim on serum levels of Leptin,CRP and lipid profile,blood sample was collected from 75 women age ranged between (15-49) years 65 of the them had hypothyroidisim while 10 of the samples were healthy control, The results showed no significant diffirence in serum Leptin (p =0.1),while there was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Table (2) shows the correlation between obesity and hypothyroidism. The research conducted by HASSAN and ABBAS (2022) revealed a negative correlation between T 3 and T 4 , but a favorable link with TSH levels and body weight and BMI [13] . Verma et al (2008) found in another study that 44% of patients with hypothyroidism were obese [14] .…”
Section: Discussionmentioning
confidence: 98%
“…Table (2) shows the correlation between obesity and hypothyroidism. The research conducted by HASSAN and ABBAS (2022) revealed a negative correlation between T 3 and T 4 , but a favorable link with TSH levels and body weight and BMI [13] . Verma et al (2008) found in another study that 44% of patients with hypothyroidism were obese [14] .…”
Section: Discussionmentioning
confidence: 98%